Effect of the Health Care Financing System on the Structure of Health Care Services - Žemgulienė, Jolanta (Ekonomika, 1999)
The article aims to assess the impact of the current changes in health care financing system on the structure of health care services. As the changes during the last two years of the number of hospitalizations and attendance of the out-patient institutions show, the incentives of the provider payment methods have the impact on the imbalancing of the health care system. The possibilities of the health care financing system to create the incentives to efficiency outcomes of health care were not used enough. The article present recommendations on the development of the health care financing administration which are helpful in creating the conditions associated with the reduction of the expenditures.